(untitled) (Proceedings of Southern Federal University. Philology, 2020)
This article considers the features of conceptual metaphor within the legal discourse. The author identifies the main approaches to the study of metaphor, in general, as well as the study of metaphor in the light of conceptual analysis, in particular. The relevance of the study is emphasized, since the problem of the functioning of conceptual metaphors within the framework of the discursive approach is poorly studied in the cognitive paradigm of modern philological scope. The article highlights the main characteristics of legal discourse, notes the features of the linguistic expression typical of this type of discourse. It is determined that the main function of a metaphor in legal discourse is to form a negative or positive opinion in the audience as a speech effect. The analysis made it possible to identify the following factors affecting the functioning of the metaphor in legal discourse, namely: period of use; reasons for intensification; historical-cultural and socio-political context; interests of actors (lawyer, judge, etc.); realized intentions. Key words: discourse, legal discourse, metaphor, conceptual metaphor, intention, function. DOI 10.18522/1995-0640-2020-2-97-102